Psychology - Davis, Stephen F. (Pearson / Prentice Hall, 2005)
Through this book's accessible, active, and applied approach, users determine whether their learning style strengths are verbal/linguistic, logical/mathematical, visual/spatial, or interpersonal, then receive personalized, content-specific study tips throughout the book! By studying according to their own personal learning style strengths, this book helps readers become more effective and efficient learners. Research updates summarize recent research from sources like Scientific American, Journal of Personality and Social Psychology, Psychological Science, Current Directions in Psychological Science, and others. A free accompanying copy of the Video Classics in Psychology CD-ROM views classic experiments like Milgram's obedience study, Watson's Little Albert, Bandura's Bobo doll, Pavlov's dogs, Harlow's monkeys, and others. Industrial/Organizational coverage is expanded to show how psychology is used in the workplace, sports, law, and real lives.